The Galician-Portuguese Fragment of the "Livro de Tristam". A New Chronological and Diatopic Proposal - Pichel, Ricardo; Varela Barreiro, Xavier (Madrygal. Revista de Estudios Gallegos, 2017)
In the study tradition of the Livro de Tristam it is commonly accepted that the Galician-Portuguese fragment belongs to the second half or to the last decades of the 14th century. Within its geographic coordinates, the studies did not go beyond in locating the copy of the manuscript in Galician territory (in opposition to the Portuguese one). By focusing our research on these two axes, the authors present in this paper a new chronological and geographic proposal supported by evidence of linguistic, paleographic and graphematic nature. These new chronological provisions place the copy into the first half of the 14th century and point out towards the last third of the 13th century as the period when the translation of its precedent was made, from French to Galician-Portuguese (very likely within the Portuguese Court). The geographic observations made narrow the geographic area of the copyist to the southern Galician land of Toroño, within the Tui diocese.